Evaluating the impact of a mindfulness based intervention on Year 5 children's social and emotional skills, optimism and mindful awareness - Whittaker, Lucy (2017)
Within existing evaluation research, mindfulness (Kabat-Zinn, 1994) has been identified as a potential intervention that could help to promote children’s wellbeing (Zelazo & Lyons, 2012). The evidence base into mindfulness interventions in schools highlights that much of the research is carried out outside of the UK. The current study therefore presents an evaluation of the impact of a mindfulness based intervention on Year 5 children’s social and emotional skills, optimism and mindful awareness. The intervention was carried out on a whole class of Year 5 children and was intended as a universal intervention to promote wellbeing (DfE, 2016). The current study adopted a mixed methods research design that used both quantitative (pupil; n=35, teacher; n=2, parent; n=33) and qualitative (n=24) investigations. The quasi-experimental quantitative strand was prioritised within the current study and was used to measure the impact of the mindfulness based intervention on self rated mindful awareness (using the Child and Adolescent Mindfulness Measure; Greco and Baer, 2006), optimism (using the Resiliency Scales for Children and Adolescents; Prince-Embury, 2006) and self, teacher and parent rated social and emotional skills (using the Strengths and Difficulties Questionnaire; Goodman et al 1998). The qualitative strand aimed to explore participants’ perceptions of the intervention through focus groups. The results showed that the mindfulness based intervention did not have a statistically significant impact on pupil rated mindful awareness or optimism but indicated a positive impact on pupil and parent rated social and emotional skills but a negative impact on teacher rated social and emotional skills. The focus groups highlighted that the intervention was perceived as a ‘sensory experience’, with participants reporting improved self and social awareness. The findings are discussed in relation to the existing literature, the methodological limitations and reliability and validity of the current study. The findings also highlight a number of potential avenues for future research and discuss a number of implications in relation to schools, local authorities and educational psychologists.